Penilaian Dampak Lingkungan Industri Tahu Menggunakan Life Cycle Assessment (Studi Kasus: Pabrik Tahu Sari Murni Kampung Krajan, Surakarta) - Elvis Umbu Lolo; Richardus Indra Gunawan; Agerippa Yanuranda Krismani; Yonathan Suryo Pambudi (Fakultas Teknik, 2021)
The problem faced by the tofu industry is waste management. So, it is necessary to do so that tofu waste does not pollute the environment by managing waste and emissions, efficient consumption of energy, materials, andwater. One way to identify environmental pollution is by Life Cycle Assessment. This study uses the Life Cycle Assessment (LCA) method. The LCA flow in this study is to determine goals and scopes, create inventory data, make grouping impacts and how much impact they generate, as well as interpreting to provide improvements. The functional unit in this study is 1 kg of tofu which is produced in 1 day. The results of this study were divided into five impact categories, namely, climate change, the most important being 2195 kg CO2, human toxicity potential at 2187 kg 1,4-Dikchloro benzene, eutrophication at 0.935 kg PO4, photo oxidant at 0.797 kg C2H4, and acidification at 15,915 kg. SO2. The recommended improvement alternative is to make efforts to use water efficiently during the tofu production process, including the need to clean the scale in the steam boiler to increase the volume of steam produced, so that the use of water and energy is more efficient.